Public Open Space Arrangement Model In Summarecon Bekasi Residential Area for Covid-19 Pandemic Mitigation - Mutia, Farah; Idawati, Dyah Erti; Achmad*, Ashfa (Aceh International Journal of Science and Technology, 2023)
The coronavirus disease in 2019 (Covid-19), a highly contagious respiratory virus, has spread to more than 200 countries and regions. The high number of Covid-19 cases has led to various regulations regarding social restrictions. Some of the changes that occurred due to the Covid-19 pandemic changed the socio-spatial structure and affected physical and psychological well-being and overall quality of life. The impact of Covid-19 has also occurred in the Summarecon Bekasi settlement, which provides facilities, a commercial center, and various public open spaces that the people of Bekasi City widely use to become more restricted. Researchers used a qualitative approach and descriptive qualitative analysis techniques with interview observations and documentation as the data sources. Research on public open spaces in Summarecon Bekasi, including downtown walk, waterfront, pedestrian paths, and bus stop shuttle bus, shows that these public spaces cannot fulfill all variable indicators of public open space readiness in dealing with post-pandemic conditions Covid-19. The results obtained are based on the weighting of values from the results of observational studies and interviews on each variable indicator of public open spaces. The empirical mean value of public open spaces in Summarecon Bekasi is 89, which is still below the hypothetical mean value of 110 and is at the lower limit of the category 'Not Enough .'Thus, to overcome the condition of public open spaces that are not yet adaptive to Covid-19, a structuring model is designed for public open spaces in Summarecon Bekasi. This structuring model is expected to reduce the percentage probability of social disasters such as the Covid-19 pandemic or other similar things.